Pengaruh Antara Waktu Penyerapan Terhadap Konsentrasi Cemaran Pb pada Daun Tanaman Bunga Matahari (Helianthus annuus L) - Purnama Dewi Rohana; Sartini Sartini; Abdul Karim (Universitas Medan Area, 2020)
Sunflowers ((Helianthus annuus L) is a plant that has the ability to absorb metals in polluted soil or environment. This study aims to determine the ability of sunflower plants to absorb lead (Pb) in the soil. This research method use a Completely Randomized Design (CRD). Pb metal analysis was carried out by testing the lrvels using the Atomic Absorption Spectrophotometry (AAS) tool in the Chemical Laboratory (LABKES). The results showed that the highest absorption of Pb contamination in P2L2 treatment (2.0 ppm) as much as 5.04 ppm and the lowest absorption of metals in the treatment P1L1 (0.3 ppm) yielded as much as 0.52 ppm Pb metal content. From the results of these studies it can be concluded that sunflower plants can be used as phytoremediation pf Pb metal.